2016
DOI: 10.1016/j.tiv.2016.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and junctional proteins of the blood-testis barrier in human Sertoli cells are modified by monobutyl phthalate (MBP) and bisphenol A (BPA) exposure

Abstract: The blood-testis barrier (BTB) is responsible for providing a protected environment and coordinating the spermatogenesis. Endocrine disruptors (EDs) might lead to infertility, interfering in the BTB structure and modulation. This study aimed to correlate the actions of two EDs, monobutyl phthalate (MBP) and bisphenol A (BPA) in different periods of exposure, in a low toxicity dose to the human Sertoli cells (HSeC) and its effects on the proteins of the BTB and regulatory proteins involved in its modulation. HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Protein expression was determined using western blot. Protein extraction was performed with RIPA lysis buffer as described previously (de Freitas et al, 2016). Aliquots (80 μg of protein) were treated with Laemli sample buffer (Bio-Rad, Hercules, CA, USA) and β-mercaptoethanol at 95°C for 1 min.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Protein expression was determined using western blot. Protein extraction was performed with RIPA lysis buffer as described previously (de Freitas et al, 2016). Aliquots (80 μg of protein) were treated with Laemli sample buffer (Bio-Rad, Hercules, CA, USA) and β-mercaptoethanol at 95°C for 1 min.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Sertoli cells are connected by gap junctions, enabling chemical and ion exchange, helping to coordinate the seminiferous epithelium cycle (Mruk and Cheng, 2004;Gao et al, 2015). Adjacent Sertoli cells are joined by tight junctions in the lateral membrane, which creates the Blood-Testis Barrier (BTB) (de Freitas et al, 2016). At the onset of meiosis, germ cells beyond the BTB move into the adluminal compartment of the seminiferous tubule, and become dependent on Sertoli cells to provide nutrients and growth factors for their development (Cheng and Mruk, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the pollutants could have crossed the blood-testis barrier (BTB) and affected the actively dividing spermatogonia resulting in damaged DNA. The plausibility of this concept is low in conjunction with the fact that (1) the arterial blood flow to the testis is rather low (about 9.6 mL/min out of a cardiac output of~4.7 L/min) [49,50] and (2) the BTB is one of the tightest blood-tissue barriers known to exist in mammalian tissues, even more difficult to cross than the blood brain barrier [51][52][53]. In fact, one of the main role of the BTB is to prevent small molecules, and hence also harmful contaminants, from passing through the paracellular space [54].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, one of the main role of the BTB is to prevent small molecules, and hence also harmful contaminants, from passing through the paracellular space [54]. On the other hand, despite being one of the strongest blood-tissue barriers, recent studies reported adverse effects of xenobiotics, such as bisphenol A and monobutyl phthalate, on Sertoli cell BTB [51,52]. To clarify this aspect, further investigation should be performed, particularly on spermatozoa, that unfortunately were not available to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the viability of TM3 cell line did not decrease significantly even after a 48 h exposure at concentrations below 50 μM. De Freitas et al [79] observed a significant reduction in the viability of human Sertoli cells after the cultivation with 10 μM BPA for 48 h.…”
Section: Bisphenol Amentioning
confidence: 95%